Sistem Pendukung Keputusan Seleksi Tim Promotion Area Berbasis Simple Additive Weighting - Hariyadi, Guruh Taufan; Aqmala, Diana; Setiawan, Aries; Farida, Ida; Hallang, Andi (Teknik Informatika Universitas Pamulang, 2021)
Promotion of direct visits to schools is spearheading the introduction of higher education products directly to teachers and students in schools. This activity requires a promotion team that is really expected to be able to introduce higher education products to attract the interest and trust of teachers, especially students, to enter the college. The problem is that so far, recruiting promotion team members is only based on subjectivity and there is no scoring system to select promotion team members objectively. A selection system is needed that is able to provide an objective assessment based on the variables of communication skills, years of service, knowledge, type of employment, area mastery, responsibility, teamwork and trust. The method used is simple additive weighting. The resulting accuracy rate is 90% from the comparison of the calculation results using the simple additive weighting method with the actual performance ratings of employees who are selected as promotion teams.